Patterns of Anemia in patients of Systemic Lupus Erythematosus Study of 75 cases from Lahore, Pakistan - MANAAL AFZAAL, ATIYA MAHBOOB, ASMA MUNIR, MONA AZIZ, MUHAMMAD USMAN (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the frequency and types of anaemia in patients of Systemic Lupus Erythematosus (SLE). Design: Cross sectional survey. Place and duration of study: Department of Haematology, PGMI/Shaikh Zayed Hospital, Lahore from May 2011 to April 2012. Patients and Methods: Seventy five diagnosed cases of SLE presenting to the in- and out-patient departments of Shaikh Zayed Medical Complex Lahore, fulfilling the inclusion criteria were included in the study. Written informed consent was taken. Patients were investigated in Haematology and Biochemistry Laboratories, Shaikh Zayed Medical Complex, Lahore. All collected information was entered into SPSS version 17.0 and analyzed using its statistical package. Results: There were 65 (86.7%) females and 10 (13.3%) male patients. Female to male ratio was 6.5:1. Age ranged from 15 to 65 years, mean 29.49±11.7 years. Most of the patients were in the age group of 15-25years. Anemia was seen in 74 patients (98.67%). Anaemia of chronic disorder (ACD) was the most common type of anemia (52.7%) followed by iron deficiency anaemia (IDA) (32.4%). Conclusion: All common types of anemia associated with SLE were recorded in the study. Complete haematological examination should be carried out in every patient of SLE for proper management and prevention of morbidity associated with anemia.